Strategies promoting mental health care in front of Covid-19 (Research, Society and Development, 2021)
Objective: to analyze the strategies promoting mental health during the pandemic by Covid-19. Methodology: Integrative literature review, which is based on the six phases established by Mendes, Silveira and Galvão, using the PCC strategy for the formulation of the northern question, and detailed and individual search conducted at Pubmed, and Latin American and Caribbean Literature on Health Sciences (LILACS) via the Virtual Health Library (VHL) in August 2021. Results: 10 articles were selected for analysis and elaboration of the synthesis matrix. Discussion: in view of the findings extracted from the selected studies, it is perceived that it is essential to take into account the social context that the person is inserted in order to identify the factors and thus be created coping strategies. Conclusion: this study allowed us to reflect on the strategies that promoting mental health, and how they have been implemented in the face of public health emergency due to the new coronavirus.